Zooming in and out the outcomes of geophysical research at the Western Tripolye culture site Kamenets-Podolskiy (Tatarysky) - Jakub Niebieszczański; Mateusz Stróżyk; Aleksandr Diachenko; Tomasz Herbich; Robert Ryndziewicz; Yevhenii Levinzon; Iwona Sobkowiak-Tabaka (Documenta Praehistorica)
This paper reports the results of magnetic surveys contextualized with the landscape via water drainage analysis, and summarizes the results of excavations at the Cucuteni-Tripolye settlement Kamenets-Podolskiy (Tatarysky), 3950–3900 BCE. Incorporation of topographic information and water drainage analysis to the studies of settlement structures revealed by magnetometry makes it possible to understand how such features function and, therefore, the intentionality behind the arrangement of houses and utility structures. The correlation between magnetic susceptibility and the mass of burnt daub coming from the individual dwelling reveals a possible weakness in interpretations, due to the influence of heat on magnetization.